-
Basic Recursion
a. Evaluate
f1a(5, 3)
=243
f1a(5, 3) > 243 - f1a(4, 3) > 81 - f1a(3, 3) > 27 - f1a(2, 3) > 9 - f1a(1, 3) > 3 - f1a(0, 3) > 1
b. Evaluate
f1b(6, 3)
=243
f1b(6, 3) > 243 - f1b(5, 3) > 81 - f1b(4, 3) > 27 - f1b(3, 3) > 9 - f1b(2, 3) > 3 - f1b(1, 3) > 1
c. Evaluate
f1c(7, 3)
=9
f1c(7, 3) > 9 - f1c(5, 3) > 3 - f1c(3, 3) > 1 - f1c(2, 3) > 1 - f1c(1, 3) > 1
-
Basic Loops
a. Evaluate
f2a(7, 3)
=6
c = 0 + 0 + 1 + 2 + 3 c = 6
b. Evaluate
f2b(3, 10)
="ZPZPZPZPZP"
s = "" = "3" = "33" = "333" = "3333" = "33333" = "333333" ... = "ZPZPZPZPZP"
c. Evaluate
f2c(3, 5)
=[3 , 2 , 2 , None, None]
l = [None, None, None, None, None] = [3 , 2 , None, None, None] = [3 , 3 , 2 , None, None] = [3 , 2 , 2 , None, None] = [3 , 3 , 2 , None, None] = [3 , 2 , 2 , None, None] = [3 , 2 , 2 , None, None]
-
Recursion with Loops
a. Evaluate
f3a(5, 3)
=[0, 0, 0, 0]
f3a(5, 3) > [0, 0, 0, 0] - f3a(4, 3) > [0, 0, 0, 0] - f3a(3, 3) > [0, 0, 0, 0] - f3a(2, 2) > [0, 0, 0] - f3a(1, 1) > [0, 0] - f3a(0, 0) > [0]
b. Evaluate
f3b(3, 2)
=['3p', '3r', '3a', '2p', '2r', '1p']
f3b(3, 2) > ['3p', '3r', '3a', '2p', '2r', '1p'] - f3b(2, 2) > ['2p', '2r', '1p'] - f3b(1, 2) > ['1p'] - f3b(0, 2) > []
c. Evaluate
f3c(5, 2)
="hi,hey,bye.hi,hey,bye."
f3c(5, 2) > "hi,hey,bye.hi,hey,bye." - f3c(4, 1) > "hey,bye." - f3c(4, 0) > "bye."